Representasi Ideologi dalam Kaidah Tafsir - Fatihullah Fatihullah (MAGHZA, 2018)
This paper discusses al-Qawā’id al-Ḥisān li-Tafsīr al-Qur’anwritten by al-Sa’di, a work with a particular format talking about interpretation rule. The interpretation rules are like a helpful tool to come with the Quran and its interpretation as such that its users can avoid from the mistake and differentiate which one is acceptable and rejected. As a tool to understand the Quran, the interpretation rule is essentially similar with usul fiqh (legal rule) in its formulation that must be scientific (verifiable), critical (non-sectarian) and objective (nonideological). This research proves that the listed rules of interpretation in al-Qawā’id al-Ḥisān li-Tafsīr al-Qur’anare not purely theoretical-objective rules, rather represent al-Sa’di’s ideological and subjective nuances.